2023
DOI: 10.3390/ncrna9010004
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Role of microRNA Mediated Regulation of Coronin 1C in Glioblastoma Development and Metastasis

Abstract: Glioblastoma multiforme (GBM) is a highly heterogenic and malignant brain tumour with a median survival of 15 months. The initial identification of primary glioblastomas is often challenging. Coronin 1C (CORO1C) is a key player in actin rearrangement and cofilin dynamics, as well as enhancing the processes of neurite overgrowth and migration of brain tumour cells. Different bioinformatic databases were accessed to measure CORO1C expression at the mRNA and protein level in normal and malignant brains. CORO1C ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
(81 reference statements)
1
2
0
Order By: Relevance
“…High levels of coronin-3 expression have previously been described to occur in diffuse gliomas. 42 Hence, the microglia cell population appears to be elevated in the wobbler mouse brain agreeing with the concept of reactive gliosis. The formation of glial scars is therefore probably associated with impaired motor neuron functions at the level of the central nervous system.…”
Section: Discussionsupporting
confidence: 68%
“…High levels of coronin-3 expression have previously been described to occur in diffuse gliomas. 42 Hence, the microglia cell population appears to be elevated in the wobbler mouse brain agreeing with the concept of reactive gliosis. The formation of glial scars is therefore probably associated with impaired motor neuron functions at the level of the central nervous system.…”
Section: Discussionsupporting
confidence: 68%
“…CORO1C acts as an F-actin turnover effector influencing neurite overgrowth and migration of brain tumor cells. 40 An elevated expression of CORO1C in metastatic malignancies, such as GB and colorectal cancer, was previously documented, indicating the potential clinical relevance of this gene as a biomarker associated with an unfavorable prognosis. 41 The negative effects of SHG-8 upon this oncogene supported the findings that SHG-8 exerted negative regulation upon de novo neurone overgrowth and the Wnt pathway, thus limiting the proliferative and migratory abilities of U87MG GB cells.…”
Section: Resultsmentioning
confidence: 89%
“…To strengthen the hypothesis that SHG-8 negatively regulated the Wnt-pathway, an in vitro RT-qPCR of CORO1C revealed that the gene was significantly downregulated in the presence of the drug. CORO1C acts as an F-actin turnover effector influencing neurite overgrowth and migration of brain tumor cells . An elevated expression of CORO1C in metastatic malignancies, such as GB and colorectal cancer, was previously documented, indicating the potential clinical relevance of this gene as a biomarker associated with an unfavorable prognosis .…”
Section: Resultsmentioning
confidence: 93%